Conclusion: Youth migration in the age of pandemic immobility - Cairns, D.; França, T.; Malet Calvo, D.; Azevedo, L. F. de (The Palgrave handbook of youth mobility and educational migration, 2022)
This concluding chapter takes account of recent developments in the field of public health. Had it not been for the global spread of Covid-19 in 2020, youth mobility might well have continued along its decades long course of global expansion and diversification, spreading into different forms of education, work and training, with the dividing line between mobility for these purposes and tourism continuing to blur. These concerns are no longer as pressing as they once were, and may not return to being high priorities for a very long time. Right now, writing in the middle of what has come to feel like an open-ended pandemic, all we can do is look at what has happened in the last few months and attempt to grasp some of the main consequences for young people who still wish or need to be mobile, in addition to engaging with the pressing problem of how to re-orient mobility practices that have stalled or never got off the ground, literally and figuratively. Additional concerns are evident in regard to how to maintain mobility systems at a time when institutions have closed their doors, again literally and figuratively, and are struggling to re-open in any meaningful sense of the word.